Melanoma-Bearing Libechov Minipig (MeLiM): The Unique Swine Model of Hereditary Metastatic Melanoma - Horak, Vratislav; Palanova, Anna; Cizkova, Jana; Miltrova, Veronika; Vodicka, Petr; Kupcova Skalnikova, Helena (Genes, 2019)
National cancer databases document that melanoma is the most aggressive and deadly cutaneous malignancy with worldwide increasing incidence in the Caucasian population. Around 10% of melanomas occur in families. Several germline mutations were identified that might help to indicate individuals at risk for preventive interventions and early disease detection. More than 50% of sporadic melanomas carry mutations in Ras/Raf/mitogen-activated protein kinase (MAPK/MEK) pathway, which may represent aims of novel targeted therapies. Despite advances in targeted therapies and immunotherapies, the outcomes in metastatic tumor are still unsatisfactory. Here, we review animal models that help our understanding of melanoma development and treatment, including non-vertebrate, mouse, swine, and other mammal models, with an emphasis on those with spontaneously developing melanoma. Special attention is paid to the melanoma-bearing Libechov minipig (MeLiM). This original swine model of hereditary metastatic melanoma enables studying biological processes underlying melanoma progression, as well as spontaneous regression. Current histological, immunohistochemical, biochemical, genetic, hematological, immunological, and skin microbiome findings in the MeLiM model are summarized, together with development of new therapeutic approaches based on tumor devitalization. The ongoing study of molecular and immunological base of spontaneous regression in MeLiM model has potential to bring new knowledge of clinical importance.
Keywords: prasata; Swine; modely nemocí na zvířatech; progrese nemoci; Skin Neoplasms; maligní melanom kůže; Disease Progression; Swine, Miniature; animal model; Neoplasms, Second Primary; Melanoma; mutation; Animals; Melanoma, Cutaneous Malignant; melanoma; zvířata; Disease Models, Animal; MeLiM; swine; nádory kůže; devitalization; genetics; progression; melanom; sekundární malignity; spontaneous regression; miniaturní prasata